2021
DOI: 10.1038/s41598-021-93841-1
|View full text |Cite
|
Sign up to set email alerts
|

Moisture variation inferred from tree rings in north central China and its links with the remote oceans

Abstract: In this study we presented a composite standard chronology, spanning 1635–2018 to reconstruct May–July moisture variation in north central China. Our reconstruction revealed four severe dry epochs and five pronounced wet epochs. Additionally, spatial correlation analysis of our reconstruction with the actual self-calibrating Palmer drought severity index showed that our reconstruction was representative of large-scale May–July moisture changes. Both the severe dry and pronounced wet epochs showed one-to-one co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Previous studies showed that a lower temperature and higher rainfall are associated with El Niño events and vice versa for La Niña events [17][18][19][20]. Dendrochronological analyses (i.e., tree ring studies) serve as important tools that can be used to investigate the influence of climatic forces on tree growth [27][28][29][30][31][32][33] and are widely used for climatic reconstructions in many regions [34][35][36][37][38][39], particularly Asia [40][41][42][43][44][45][46]. The understanding of Thai tree-growth dynamics has been limited in space and time due to the scarcity of long-term tree-growth data (e.g., [47]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that a lower temperature and higher rainfall are associated with El Niño events and vice versa for La Niña events [17][18][19][20]. Dendrochronological analyses (i.e., tree ring studies) serve as important tools that can be used to investigate the influence of climatic forces on tree growth [27][28][29][30][31][32][33] and are widely used for climatic reconstructions in many regions [34][35][36][37][38][39], particularly Asia [40][41][42][43][44][45][46]. The understanding of Thai tree-growth dynamics has been limited in space and time due to the scarcity of long-term tree-growth data (e.g., [47]).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we explore multi‐timescale natural variability in coastal flooding through innovative uses of the paleorecord to reconstruct plausible sequences of water levels and the likelihood of coastal flood events. Past studies have used a combination of tree rings and marine and nearshore paleo proxies, including geochemical proxies, to reconstruct total seasonal precipitation (Chen et al., 2015; Neukom et al., 2014; Williams et al., 2021), extreme precipitation (Borkotoky et al., 2021; Steinschneider et al., 2016, 2018), regional moisture transport (Mukhopadhyay et al., 2018; Zheng et al., 2021), drought (Baek et al., 2019; McCabe et al., 2008; Woodhouse et al., 2010), global surface temperature (Osman et al., 2021), terrestrial climate (Krapp et al., 2021), SSTs (Emile‐Geay et al., 2013, 2015; Freund et al., 2019), and sea surface salinity (Nurhati et al., 2011). These studies rely on robust relationships between environmental signals embedded within networks of paleo‐proxies and large‐scale oceanic and atmospheric conditions that determine the likelihood of those environmental responses.…”
Section: Introductionmentioning
confidence: 99%